Need of Gene library system in Sri Lanka–a librarian’s perspective. - Navaneethakrishnan, S.; Mythili Devi, G. (M.M.University Mullana Ambala, India., 2014)
Nowadays gene libraries are becoming a crucial part of the long-term infrastructure of biomedical and health research of a nation. A random collection of DNA fragments, typically representing the entire genome of an organism, that have been inserted into a cloning vector are called as gene libraries. Gene libraries are sometimes called as gene banks or genomic libraries. Health ministry of Sri Lanka plays a vital role in developing such libraries to contribute to health research and to build a healthy nation that contributes to the development. Librarians also have to think creatively about developing increased effective collaboration for the development of such library system. This will expand the role of the library as a new tool for the development. In view of that the purpose of this research is to shed light on Gene library system for Sri Lanka, which could be achievable by the collaborative effort of Health and Library professions of Sri Lanka. Health researchers need to get information and samples from large numbers of people in their investigation of the complex effects that genes can have on our health. This information is not always easy to get and collecting it often costs a lot of scarce time and money. The objective of this research is to identify the need of the Gene library system in Sri Lanka and to emphasis to start the process of a national scheme for the development of this Library system, based on international recommendations and standards. Based on survey on literatures and current library system in Sri Lanka, this study emphasizes some significant and basic need of gene library in Sri Lanka. This study reveals for Sri Lanka has to establish a gene library system with at least ten thousand DNA and blood samples collected from volunteers throughout the nation, the results of a detailed medical examination and answers to a questionnaire on aspects of their lifestyle and environment. This combination of both samples and health information will make the library especially useful. Policy decision should be made at national level for gene library, which will be an almost inexhaustible resource for research; with careful management. It will serve as a large sample, providing essential health information that will be representative of the population of the nation. It will help health research organizations to achieve results more quickly, and to be more efficient and cost effective. It will be a powerful and valuable resource for health research of the nation and will lead to discoveries about the causes of disease, new diagnostic tests, and new drugs. With the help of gene library, genetic testing can be done which can confirm or rule out a suspected genetic condition or help determine a person’s chance of developing or passing on a genetic disorder. Researchers are able to conduct their studies more quickly and efficiently and avoid duplication.
Keywords: Library Science; Gene Libraries; Information Services; Sri Lanka